Murder in the family - Hunter, Cara (William Morrow, an imprint of HarperCollins Publishers, 2023)
"In December 2003, Luke Ryder, the stepfather of acclaimed filmmaker Guy Howard, was found dead in the garden of their suburban family home. Guy was only a child, asleep upstairs at the time of the murder. His mother and two half sisters were also in the house that night -- but all swear they saw nothing. Despite a high-profile police investigation and endless media attention, no suspect was ever charged, and Guy's family has been haunted ever since. Twenty years later, the sensational new streaming series Infamous is dedicated to investigating -- and perhaps cracking -- this famous cold case. The production team will reexamine testimony, reinterview witnesses, and once again scour the evidence. The family will speak. The key players will be reunited -- on camera. The truth will come out. Are you ready to see it?" --